Impact of pharmacokinetics on the toxicity and efficacy of clofarabine in patients with relapsed or refractory acute myeloid leukemia. Issue 12 (2nd December 2017) - Büttner, Bozena; Knoth, Holger; Kramer, Michael; Oertel, Reinhard; Seeling, Andreas; Sockel, Katja; von Bonin, Malte; Stölzel, Friedrich; Alakel, Nael; Platzbecker, Uwe; Röllig, Christoph; Ehninger, Gerhard; et al.
Abstract: Common side effects of clofarabine (CFB) are liver toxicity, particularly a transient elevation of transaminases and skin toxicity. We studied the correlation of pharmacokinetic (PK) parameters with these toxicities and the efficacy of CFB in patients with relapsed or refractory acute myeloid leukemia. Clofarabine PK parameters showed large inter-individual variability. A higher CFB area under the curve was significantly associated with higher transaminase levels ( p = .011 for aspartate aminotransferase (AST), adjusted for age, sex, cumulated CFB dosage, baseline AST, and glomerular filtration rate (GFR)). No significant association could be found between maximum concentration and the liver toxicity parameters. The occurrence of skin toxicity and the response to re-induction chemotherapy evaluated at day 15 were also not associated with PK. In conclusion, a higher individual CFB exposure is associated with increased liver toxicity reflected by elevated liver enzymes, without having an impact on anti-leukemic efficacy.